Potentially inappropriate medications and potential prescribing omissions. Identification and relevance. - Soraia Azevedo; Rosana Maia; Emília Guerreiro (Sociedade Galega de Medicina Interna, 2020)
Introduction: Europe presents 19% of the population aged 65 or over (elderly), who are especially susceptible to inadequate prescriptions (potentially inappropriate medications (PIM) and potential prescribing omissions (PPO)), identified by the STOPP and START criteria. This study has as main objectives the identification of PIM and PPO and associated factors. Material and Methods: This is a cross sectional study, using a sample of 254 elderly individuals from the Internal Medicine Service. Results: 81.9% of patients are polymedicated, 72.4% have at least one PIM and 57.5% have at least one PPO. The most frequently identified PIM was benzodiazepine and PPO was the anti-pneumococcal vaccine. There was a direct correlation between the number of PIM and chronic medication (r(254)=0.348, p<0.001) and inverse with the Katz scale (dependence) (r(254)=-0.324, p<0.001). In the cases of the domicile it was verified association between PIM and the days of internment (U=3653, p=0.025). PIM were associated with death in less than 6 months after discharge (U=3396, p=0.007) and the presence of intercurrences at admission (U=5766, p=0.005). There is a relationship between the number of co-morbidities and having at least one PIM (U=5378, p=0.041) or at least one PPO (U=6271, p=0.005). Diabetes mellitus (DM) type 2, neurological and psychiatric disease are associated with PIM, while obesity, DM type 2, arterial hypertension, dyslipidemia and cardiac pathology with PPO. Discussion and Conclusion: In a population that is older each year, with more comorbidities and more polymedicated, PIM and PPO are increasingly relevant.